2019
DOI: 10.1515/cclm-2018-1197
|View full text |Cite
|
Sign up to set email alerts
|

The effect of DOAC-Stop on lupus anticoagulant testing in plasma samples of venous thromboembolism patients receiving direct oral anticoagulants

Abstract: Background Direct oral anticoagulants (DOACs) cause false positive lupus anticoagulant (LA) results. We assessed the impact of DOAC-Stop, reversing in vitro effects of DOACs, on LA testing in anticoagulated patients. Methods We assessed 75 venous thromboembolism patients aged 44.5±14.6 years. Blood samples were collected 2–28 h since intake of DOACs, including 50 patients on rivaroxaban, 20 on dabigatran and five on apixaban. LA testing was performed at baseline and after DOAC-Stop treatment. Positive LA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 25 publications
5
53
1
Order By: Relevance
“…There were relatively small numbers of patients in the validation of DOAC‐Remove; however, this is likely to reflect real world experience of reference laboratories. In addition, as already described, there are other studies which have validated another charcoal DOAC neutraliser (DOAC Stop) (Kopatz et al , ; Zabczyk et al , ). Our study did not incorporate warfarin into the algorithm, however we believe this is probably not problematic.…”
Section: Discussionmentioning
confidence: 92%
“…There were relatively small numbers of patients in the validation of DOAC‐Remove; however, this is likely to reflect real world experience of reference laboratories. In addition, as already described, there are other studies which have validated another charcoal DOAC neutraliser (DOAC Stop) (Kopatz et al , ; Zabczyk et al , ). Our study did not incorporate warfarin into the algorithm, however we believe this is probably not problematic.…”
Section: Discussionmentioning
confidence: 92%
“…DOAC Stop has been assessed for DOAC neutralization in several studies, but mostly related to assessment of thrombophilia, 18,19,[26][27][28][29][30][31] and included in only a few studies related to factor assays. 30,32 To our knowledge, no study has previously assessed the effect of andexanet alfa on factor levels and DOAC interference.…”
Section: Discussionmentioning
confidence: 99%
“…No alternatives exist for LA detection in samples containing direct thrombin inhibitors. Some studies have suggested that absorption methods to remove the DOACs are effective (Exner et al ., ; Cox‐Morton et al ., ; Platton & Hunt, ; Zabczyk et al ., ) but none of these methods are validated in a large number of samples from true positive and negative patients with APS.…”
Section: Recommendationsmentioning
confidence: 99%